Penggunaan Media Video Tutorial Photoshop Untuk Meningkatkan Hasil Belajar Siswa Pada Mata Pelajaran Perwajahan Desain Di SMK - Ervianti Ervianti; Muh Putra Pratama; Nurhikmah H, Nurhikmah H,; Rosihan Aminuddin (Department of Electrical Engineering, University of Patria Artha, 2022)
The purpose of this study was to determine the effect of using Photoshop tutorial on student learning outcomes in the subject of class XI Design at SMK Negeri 1 Pallangga, Gowa Regency. The approach used in this study is a quantitative approach, with the type of experimental, and the research design used is the pretest posttest group design, which compares the results of the pretest and posttest in the control class and the experimental class. The population in this study amounted to 58 people, consisting of 28 women and 20 men. The sampling technique used is a random sampling technique, which takes all population groups randomly as a sample. Data collection techniques used are observation, tests, and documentation. The data analysis used is descriptive statistical analysis and inferential statistical analysis using SPSS. The results of this study indicate that there is a significant difference between after using the photoshop tutorial in the face subject, photoshop editing material in the experimental class compared to the control class. This at the same time answers the hypothesis